Primary Maxillofacial Large B-Cell Lymphoma in Immunocompetent Patients: Report of 5 Cases - Ines Velez; Maritzabel Hogge (Case Reports in Radiology)
Lymphomas of the oral cavity represent 5% of all lymphomas. They usually occur in immunocompromised patients. Lymphoma arising within a single bone, without visceral or lymph node involvement, is known as primary intraosseous lymphoma. It is a rare condition and constitutes 3.1% of malignant bone tumors and 5% of extranodal lymphomas. Primary lymphoma of the jaw is seldom seen and it is often misdiagnosed. Clinically, the manifestations are usually similar to an odontogenic tumor, cyst, or infection. Radiographically it appears as a radiolucent area that may mimic endodontic lesion, periodontal pathology, or odontogenic cyst or tumor. The initial presentation is commonly followed by multiple unnecessary extractions and/or root canal treatments. We present five cases of rare primary lymphoma of the maxillofacial complex, four of them intraosseous.